(untitled) (Research, Society and Development, 2023)
The focus of this work was the elaboration of a product applicable to the teaching of Chemistry in basic education, prioritizing the investigative-experimental approach. We sought to investigate, in a second grade high school class, how the use of the developed product, from an investigative perspective, enriches the Chemistry teaching process and promotes meaningful learning. In this way, a didactic sequence was developed in which the teacher acts as a mediator of the process, experiencing a horizontal working condition, in which the student is the subject of his own learning. The topic addressed was electrochemistry, with an emphasis on conductance measurements and electrolysis execution. The assessments of prior learning and after the application of the didactic sequence were developed to obtain a parameter for comparing the knowledge built throughout the process. The educational product, called an electrochemistry kit, was developed by the students themselves, accompanied by the researcher professor, with materials reused from the electronic waste and allowed its use by teachers in schools that have or not a Chemistry laboratory. The adoption of this work methodology for the teaching of electrochemistry allowed a range of discussions in the classroom, since the didactic sequence adopted touched environmental Chemistry.